2013
DOI: 10.3748/wjg.v19.i1.65
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged QT dispersion in inflammatory bowel disease

Abstract: Our data show that IBD patients have prolonged QTcd in relation to controls. The routine follow-up of IBD patients should include determination of HOMA, insulin values and electrocardiogram examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Figure 4 shows the PRISMA diagram summarizing the sequence of the literature selection. Seven studies reported on QTc interval [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Table 3 summarizes the results of the studies that measured the QTc interval in patients with IBD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 shows the PRISMA diagram summarizing the sequence of the literature selection. Seven studies reported on QTc interval [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Table 3 summarizes the results of the studies that measured the QTc interval in patients with IBD.…”
Section: Resultsmentioning
confidence: 99%
“…Population-based studies demonstrate that disease activity in IBD is associated with an increased risk of morbidity and mortality due to CVD [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Furthermore, a number of observations indicate that patients with IBD are at a higher risk of developing ECG abnormalities, i.e., QTc interval [ 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. QTc interval represents the most investigated ECG parameter in patients with IBD [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, UC and CD can show similar autonomic and ECG alternations owing to their same mechanisms of tissue damage [32]. …”
Section: Discussionmentioning
confidence: 99%